Ketahanan Toleransi Orang Jawa: Studi tentang Yogyakarta Kontemporer - Putro, Zaenal Abidin Eko (UI Scholars Hub, 2010)
This paper aims to elaborate the tolerance discourse in Yogyakarta through restricted research pertaining that issue within the society of Yogyakarta. Since the beginning, the society of Yogyakarta has been practiced brotherhood, fraternity and tolerance in many ways. In early 1990s, however, some Islamist group has been growing at the city in which a number of Islamic schools and hospitals were built in some area in Yogyakarta. Religious mass organizations that have existed previously, for instance Muhammadiyah, in some cases, distressed by Islamist group movements. The organizations seem to be victimized by the militants and they were vulnerable from recent renewing Islamism in global context. Surprisingly, in society itself, a number of local wisdom that has to do with tolerance discourse still spreads enormously. It’s dealt with verbal speech (pitutur) generating from predecessor to successor inhabitant, from Mataram Kingdom to recently, Daerah Istimewa Yogyakarta (DIY).